2009
DOI: 10.5713/ajas.2009.70457
|View full text |Cite
|
Sign up to set email alerts
|

Association between Single Nucleotide Polymorphisms in the Dgat2 Gene and Beef Carcass and Quality Traits in Commercial Feedlot Steers

et al.

Abstract: Diacylglycerol acyltransferase (DGAT) is a key enzyme that catalyzes the final and rate-limiting step of triglyceride synthesis. Both DGAT1 and DGAT2 genes code proteins with DGAT activity. Studies have shown DGAT1 polymorphisms associate with intramuscular fat deposition in beef cattle, but fewer associations between DGAT2 and beef cattle economic traits have been reported. The objective of this study was to investigate single nucleotide polymorphism (SNP) in intron3 of bovine DGAT2 and evaluate the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The association between variation in DGAT2 and the various quantitative traits related to TG synthesis and storage has been recently reported in a number of other animal species. Li et al [11] found that SNPs in intron 3 of DGAT2 were associated with the body weight and fat yield in commercial feedlot steers. Yin et al [15] and Li et al [16] reported that a SNP and 13 bp indel in the 3′-UTR of DGAT2 were associated with backfat thickness and lean percentage in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between variation in DGAT2 and the various quantitative traits related to TG synthesis and storage has been recently reported in a number of other animal species. Li et al [11] found that SNPs in intron 3 of DGAT2 were associated with the body weight and fat yield in commercial feedlot steers. Yin et al [15] and Li et al [16] reported that a SNP and 13 bp indel in the 3′-UTR of DGAT2 were associated with backfat thickness and lean percentage in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The bovine DGAT2 maps to chromosome 15q25–q26 [10] and numerous variations have been detected in cattle [10,11,12]. The expression of DGAT2 is positively correlated to intramuscular fat (IMF) content in longissimus dorsi muscles of Korean steers [13] and pigs [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine DGAT2 has been mapped to BTA15q25-26 by fluorescence in situ hybridization (FISH) (Winter et al, 2003). Studies have shown that the polymorphisms of DGAT2 gene were associated with economic traits in some domestic animals, such as carcass, meat quality, and fat yield traits in commercial feedlot steers (Li et al, 2009); back-fat thickness in pigs (Yin et al, 2012); carcass weight and shear force in domestic pigeons (Mao et al, 2018); body weight and length in cattle (Zhang et al, 2007;Mao et al, 2008); and milk yield and fat percentage in goats (An et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the DGAT1 and DGAT2 play fundamentally different roles in mammalian TAG metabolism (Stone et al, 2004). The DGAT2-specific functions are still poorly understood in livestock, but some recent evidence associated it with carcass fat in commercial feedlot steers (Li et al, 2009) and more recently a genome-wide association study on IH have indicated a marker of milk protein percentage close to the DGAT2 gene (Capomaccio et al, 2015).…”
Section: Pathway Interpretation In Is Cowsmentioning
confidence: 97%